Solving area-based problems through intellectual empowerment: a model for developing village health volunteers’ and public health officials’ competencies in producing academic work - Kittiporn Nawsuwan; Noppcha Singweratham; Natthawut Suriya; Roshinee Oupra (Scientific Reports)
Abstract This action research aimed to analyse the situation, create, develop, and evaluate the model. Furthermore, reporting the lessons learned from the outcomes. The sample group, chosen through purposive sampling, consisted of 10 village health volunteers and 10 public health officers, all attending sub-district health promotion hospitals. The research tools were a questionnaire on academic performance productivity and records of the participants’ academic work. These obtained an IOC value between 0.67 and − 1.00, while the Cronbach’s alpha confidence coefficients were 0.84 and 0.86, respectively. The study followed the steps of action research. The data were analysed using descriptive statistics, Wilcoxon signed-rank test statistics, content analysis, and thematic analysis. The results were as follows: 1. Before using the model, the VHVs had the highest capacity in terms of character traits conducive to academic work performance ( $$\bar{x}$$ = 3.24, SD = 0.43), while the public health officials had the highest score regarding attitude towards developing routine work in research (x¯= 3.70, SD = 0.69). VHVs showed increased competency scores (Z = -2.803, p = 0.005; effect size r = 0.63), and public health officials improved in R2R competency (Z = -2.497, p = 0.013; effect size r = 0.56). The qualitative data consisted of (a) problems in producing academic works, (b) the need for academic knowledge, (c) academic potential, (d) obstacles to producing academic works, (e) needs for academic work production, and (f) competencies necessary for academic work production. 2. The model consisted of 5 Ps, namely (a) policy formulation from supervisors, (b) preparation, (c) practice, (d) publication of academic works, and (e) positive reinforcement. 3. After the development of the model, both VHVs and public health officials showed higher competencies to produce academic works than before using the model, with statistical significance at the 0.01 and 0.05 levels, respectively. 4. For the VHVs and public health officials, the key success factors for producing academic works were (a) setting a clear policy, (b) preparation, (c) practical implementation, (d) having a mentor to support academic work production, and (e) using positive reinforcement. Conclusion, the ability of village health volunteers (VHVs) and public health officials to generate academic work is crucial for addressing health issues in a specific area. To enhance their competencies, a model should be employed that involves developing strategic and action plans and organizing workshops. These workshops will encourage the creation of academic work aimed at solving local health problems based on academic principles. These findings suggest that the model effectively strengthens the academic capacity of frontline health workers. The intervention holds potential for scaling within public health policy frameworks to foster evidence-based practices and community-driven health solutions across diverse settings.